2013
DOI: 10.1117/1.jbo.18.5.055004
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer and light diffusion through dentin in photodynamic therapy

Abstract: Abstract. Photodynamic therapy has been considered a potential antimicrobial modality against oral infections, including dental caries. A model to estimate the penetration of both photosensitizers and light through human dentin, a factor of interest in photodynamic therapy, is proposed. The photoacoustic spectroscopy technique was used to evaluate in vitro dentin permeability of three different photosensitizers. Using the dentin optical absorption and scattering coefficients, it was possible to propose a semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…The optical absorption band of TB extended from 500 nm to 700 nm. The visible absorption maximum ( max ) of TB was 630 Ϯ 4 nm; max of TB were also observed at 570 nm and 650 nm (24). The optical absorption measurement of Ce6 revealed maximum absorption peaks at around 403 Ϯ 2 nm (Soret band) and 664 Ϯ 3 nm (Q band), respectively (25).…”
Section: Methodsmentioning
confidence: 95%
“…The optical absorption band of TB extended from 500 nm to 700 nm. The visible absorption maximum ( max ) of TB was 630 Ϯ 4 nm; max of TB were also observed at 570 nm and 650 nm (24). The optical absorption measurement of Ce6 revealed maximum absorption peaks at around 403 Ϯ 2 nm (Soret band) and 664 Ϯ 3 nm (Q band), respectively (25).…”
Section: Methodsmentioning
confidence: 95%
“…It has been shown that the penetration of toluidine blue and methylene blue in healthy dentin are, respectively, 130 and 190 µm, 26 and this penetration is even smaller in the carious dentin, only 52.6 µm below the surface. 27 Therefore, the altered structure of the carious dentin may not allow adequate penetration of the photosensitizer 28,14 and its interaction with microorganisms such as the ones in the mutans group, which have been observed in dental tubules at depths of 200 µm or more from the dentinal surface.…”
mentioning
confidence: 99%
“…Besides, this visual method of cross‐section samples is destructive, it lacks spatial resolution and it is time consuming . The photoacoustic spectroscopy (PAS) technique expressed by a semiquantitative model also has been proposed; however, the demineralized tissues were not taken into account during the analysis .…”
Section: Discussionmentioning
confidence: 99%